2020
DOI: 10.1093/bjsw/bcaa150
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Burnout and Job Satisfaction in a Sample of Spanish Social Workers

Abstract: Burnout and its relationship with job satisfaction have been addressed extensively. Research has focused mainly on diverse groups such as health care workers, teachers and (more recently) social workers. This study aims to examine the relationships between the dimensions of burnout and job satisfaction amongst social workers. A sample of 947 Spanish social workers was collected. We used a structural equation model using the partial least squares structural equation modelling approach. A series of hypotheses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In the social work domain, there has been a lack of clarity on how the mechanism of social support influence WFC and LS. By mitigating social workers' stress or strain [11,29], social support protects social workers from negative work experiences, such as burnout [5,68] and promotes subjective well-being [9]. Of the few studies that considered WFC, one revealed that social workers took advantage of work support to cope with WFC [15].…”
Section: The Protective Role Of Work Supportmentioning
confidence: 99%
“…In the social work domain, there has been a lack of clarity on how the mechanism of social support influence WFC and LS. By mitigating social workers' stress or strain [11,29], social support protects social workers from negative work experiences, such as burnout [5,68] and promotes subjective well-being [9]. Of the few studies that considered WFC, one revealed that social workers took advantage of work support to cope with WFC [15].…”
Section: The Protective Role Of Work Supportmentioning
confidence: 99%
“…Prior to the pandemic, social workers were already in a high-risk category for developing mental health and well-being-related problems (Truter and Fouche, 2021;Dominelli, 2021;Harrikari et al, 2021;Savaya et al, 2021). There was substantial evidence internationally that social workers faced intense workplace job demands and chronic stress (Kim and Lee, 2009;Johnson et al, 2019Johnson et al, , 2020, face burnout (McFadden et al, 2015;Go ´mez-Garcı ´a et al, 2020) and are influenced strongly by negative psychological impact (Evans et al, 2006;Harrikari et al, 2021;Savaya et al, 2021). A survey of its members by the British Association of Social Work (BASW, 2021) reported that 58.8 percent of social workers surveyed considered that working during the COVID-19 crisis had negatively impacted their mental health while 68.3 percent said it was more difficult working at home than when in the office.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, another intriguing finding of this study is that although workplace ostracism cannot directly predict job satisfaction, it can indirectly influence job satisfaction through job burnout. Previous studies have indicated that job burnout has a negative and significant effect on job satisfaction (Chong and Monroe, 2015 ; Lu and Gursoy, 2016 ; Gomez-Garcia et al, 2021 ). In addition, we also find that the link between workplace ostracism and KSBs is sequentially mediated by job burnout and job satisfaction, which further confirms the underlying mechanism linking workplace ostracism and KSBs.…”
Section: Discussionmentioning
confidence: 97%